Hopf Algebras - Radford, David E (New Jersey : World Scientific, 2012)
The book provides a detailed account of basic coalgebra and Hopf algebra theory with emphasis on Hopf algebras which are pointed, semisimple, quasitriangular, or are of certain other quantum groups. It is intended to be a graduate text as well as a research monograph.
Includes Bibliography 537-550p.and Index 551-559p.
Keywords: Hopf algebras; Mathematics; General Science